Autoimmune epilepsy - О. S. Shilkina; E. A. Kantimirova; A. A. Usoltseva; Т. I. Prusova; D. V. Dmitrenko (Эпилепсия и пароксизмальные состояния)
Investigation of autoimmune epilepsy (AIE) has been attracting increasingly more attention due to discovery of neuronal antibodies and improved understanding of the mechanisms related to such immune-mediated syndromes. The review is aimed at autoimmune epilepsy taking into account up-to-date advances  in exploring its pathophysiology. Definitions related to this issue are outlined, and pathogenetic mechanisms, features of antineuronal antibodies as well as AIE clinical picture based on type of autoantibodies, are considered. The necessity of regular monitoring patients with AIE is indicated, preferably by an epileptologist  together  with a neuroimmunologist.  With prolonged  follow-up,  chronic  pharmacoresistant  epilepsy persists in some  patients, despite aggressive immunotherapy and antiepileptic drugs. With a deeper understanding of the mechanisms of antibody-mediated and autoantigen-specific T-cell-mediated AIE syndromes, the use of antiepileptic drugs and immunotherapy can be further optimized.